Idiopathic‐generalized epilepsy shows profound white matter diffusion—tensor imaging alterations. Issue 7 (6th November 2013) - Focke, Niels K.; Diederich, Christine; Helms, Gunther; Nitsche, Michael A.; Lerche, Holger; Paulus, Walter
Abstract Objectives Idiopathic‐generalized epilepsy (IGE) is currently considered to be a genetic disease without structural alterations on conventional MRI. However, voxel‐based morphometry has shown abnormalities in IGE. Another method to analyze the microstructure of the brain is diffusion‐tensor imaging (DTI). We sought to clarify which structural alterations are present in IGE and the most frequent subsyndrome juvenile myoclonic epilepsy (JME). Experimental design We studied 25 patients (13 IGE and 12 JME) and 44 healthy controls with DTI. Fractional anisotropy (FA), mean diffusivity (MD), axial and radial diffusivity (AD/RD) were calculated and group differences were analyzed using tract‐based spatial statistics (TBSS). Additionally we performed a target‐based classification of TBSS results based on the Freesurfer cortical regions. Principle observations TBSS showed widespread FA reductions as well as MD and RD increases in patients compared to controls. Affected areas were corpus callosum, corticospinal tract, superior and inferior longitudinal fasciculus and supplementary motor regions. No significant differences were found between JME and IGE subgroups. The target‐based classification confirmed a particular involvement of the superior frontal gyrus (mesiofrontal area) in IGE/ME. Conclusions IGE and JME patients showed clear microstructural alterations in several large white matter tracts. Similar findings have been reported in rodent models of IGE. Previous, region‐of‐interest‐based DTI studies may have under‐estimated the spatial extent of structural loss associated with generalized epilepsy. The comparison of clinically defined JME and IGE groups revealed no significant DTI differences in our cohort. Hum Brain Mapp 35:3332–3342, 2014. © 2013 Wiley Periodicals, Inc.